Evaluating the Association of TORCH Infection with Bad Obstetric History among Pregnant Women in India - Panwar , Bhanu Priya; Bithu, Rameshwari; Yadav, Manju; Maheshwari , Rakesh Kumar; Malhotra , Bharti (Emerging Trends in Disease and Health Research Vol. 8, 2022)
Congenital infections refer to those infections which can transmit from mother to fetus in utero and lead to serious feotal outcomes. These infections are TORCH infections which include toxoplasma, rubella, cytomegalovirus and herpes simplex virus type 1 and 2. Congenital infections are prevented by early antenatal diagnosis and proper management. The aim of this study was to evaluate the association of TORCH infection with bad obstetric history among pregnant women. This is an Observational and comparative study This study was conducted at Central laboratory section of Department of Microbiology, SMS Medical College and Attached Group of Hospitals, Jaipur (Rajasthan) between April 2020 and September 2021. Blood samples were taken from 260 pregnant women (130 with a negative obstetric history and 130 without a negative obstetric history). Chemiluminescence was used to detect IgM and IgG antibodies against Toxoplasma, Rubella, and Cytomegalovirus, as well as ELISA for Herpes simplex virus 1 and 2. The findings of this study revealed that Overall TORCH IgM seropositivity in high-risk pregnant women was 17.19%. In pregnant women with bad obstetric history, IgM Seropositivity for Toxoplasma gondii was 3.84% (P value .02), rubella 2.34% (P value .30), Cytomegalovirus 5.47% (P value .08), and 6.25% (P value .56) for Herpes-1 and 2 infections and IgG seropositivity for toxoplasma, rubella, cytomegalovirus and herpes virus was 16.41% (P value .001), 93.75% (P value .11), 98.44% (P value .55), 48.44% (P value .53) respectively. In pregnant women without bad obstetric history, IgM and IgG seropositivity for toxoplasma, rubella, cytomegalovirus and herpes virus was 0/0.77%, 0.76/97.69%, 1.53/99.23% and 4.61/44.62% respectively. It is concluded that TORCH infection is transmissible in-utero in all the stages of pregnancy which causes serious outcomes in both mother and fetus. So early diagnosis and prompt treatment is necessary for healthy pregnancy and better feotal outcomes.